x → ∞ lim ( ( 1 + x ) 2 + ( 1 − x ) 2 ) 3 2 ( ( 1 + x ) 5 + ( 1 − x ) 5 ) ( ( 1 + x ) 3 + ( 1 − x ) 3 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same way.
The limit will depend only on the highest powers of x, so we don't need to expand the whole thing: It's easy to see that the x 5 and the x 3 terms above will cancel each other, so the highest-degree terms lead to: L i m = ( 2 x 2 ) 3 2 ( 1 0 x 4 ) ( 3 x 2 ) Which is 15.
only by divided by x^6 in up and down after u finshed ( ) there also quickly method like that
⇒ ( 1 + x ) 2 + ( 1 − x ) 2 = 1 + 2 x + x 2 + 1 − 2 x + x 2 = 2 x 2 + 2
⇒ ( 1 + x ) 3 + ( 1 − x ) 3 = ( 1 + x + 1 − x ) [ ( 1 + x ) 2 − ( 1 + x ) ( 1 − x ) + ( 1 − x ) 2 ] = 2 ( 2 x 2 + 2 − 1 + x 2 ) = 6 x 2 + 2
Since,
[ ( 1 + x ) 2 + ( 1 − x ) 2 ] [ ( 1 + x ) 3 + ( 1 − x ) 3 ] = ( 1 + x ) 5 + ( 1 − x ) 5 + [ ( 1 + x ) ( 1 − x ) ] 2 ( 1 + x + 1 − x )
Thus,
⇒ ( 1 + x ) 5 + ( 1 − x ) 5 = ( 2 x 2 + 2 ) ( 6 x 2 + 2 ) − 2 ( 1 − x 2 ) 2 = 1 2 x 4 + 1 6 x 2 + 4 − 2 x 4 + 4 x 2 − 2 = 1 0 x 4 + 2 0 x 2 + 2
From Limit,
x → ∞ lim [ ( 1 + x ) 2 + ( 1 − x ) 2 ] 3 2 [ ( 1 + x ) 5 + ( 1 − x ) 5 ] [ ( 1 + x ) 3 + ( 1 − x ) 3 ] = = = = = x → ∞ lim ( 2 x 2 + 2 ) 3 2 ( 1 0 x 4 + 2 0 x 2 + 2 ) ( 6 x 2 + 2 ) x → ∞ lim 8 ( x 2 + 1 ) 3 8 ( 5 x 4 + 1 0 x 2 + 1 ) ( 3 x 2 + 1 ) x → ∞ lim x 6 + 3 x 4 + 3 x 2 + 1 1 5 x 6 + 3 5 x 4 + 1 3 x 2 + 1 x → ∞ lim 1 + x 2 3 + x 4 3 + x 6 1 1 5 + x 2 3 5 + x 4 1 3 + x 6 1 1 5
Problem Loading...
Note Loading...
Set Loading...
L = x → ∞ lim ( ( 1 + x ) 2 + ( 1 − x ) 2 ) 3 2 ( ( 1 + x ) 5 + ( 1 − x ) 5 ) ( ( 1 + x ) 3 + ( 1 − x ) 3 ) = x → ∞ lim 8 ( 1 + x 2 ) 3 8 ( 1 + 1 0 x 2 + 5 x 4 ) ( 1 + 3 x 2 ) = x → ∞ lim 1 + 3 x 2 + 3 x 4 + x 6 1 + 1 3 x 2 + 3 5 x 4 + 1 5 x 6 Divide up and down by x 6 = x → ∞ lim x − 6 + 3 x − 4 + 3 x − 2 + 1 x − 6 + 1 3 x − 4 + 3 5 x − 2 + 1 5 = 1 5